Can Beliefs and Realities Be Bridged? A Study of Culturally Responsive English Literacy Education in Rural Papua - Ningsih, Sri Kusuma; Setyarini, Sri; Gustine, Gin Gin (Universitas Hamzanwadi, 2025)
English literacy education in rural Papua, Indonesia, presents unique challenges shaped by geographical isolation, ethnolinguistic diversity, and limited resources. While previous studies have examined EFL teaching challenges in Indonesia, little research has explored how teachers' pedagogical beliefs interact with contextual constraints in rural settings. This study investigates the nexus between English as a Foreign Language (EFL) teachers’ beliefs and classroom practices in resource-constrained environments. Employing a qualitative case study approach, data were collected from X teachers through classroom observations, semi-structured interviews, and document analysis. Findings reveal a persistent gap between teachers’ pedagogical beliefs and their ability to implement them due to contextual constraints, including inadequate teaching materials and a rigid national curriculum. Teachers who incorporated local cultural elements, such as Papuan folktales and proverbs, into their lessons demonstrated higher student engagement and improved literacy outcomes. These culturally responsive practices bridge students’ linguistic realities and the English literacy curriculum, fostering a deeper connection to the learning process. However, systemic barriers, including insufficient professional development and the absence of culturally relevant teaching materials, limit the broader adoption of these practices. This study underscores the need for flexible curricula that integrate local cultural content and calls for increased institutional support to equip teachers in rural areas. Addressing these challenges is crucial for improving English literacy education in rural, multilingual contexts, ensuring equitable learning opportunities for all students.